TRAINING MODEL OF PRIMARY SCHOOL TEACHERS TO FORMATION OF CONSTRUCTIONAL SKILLS YOUNGER STUDENTS - Оlesia Oliinyk (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2017)
The term "model" is defined on the base of the analysis of works of scientists. The essence of the modeling process as a method of research of pedagogical phenomena and processes, establishing properties and relationships between all components of the educational-cognitive activity are clarified. It is established that the model of training of future primary school teachers to the formation of constructive skills graphically displays the structure and contents of the mentioned training, justification of pedagogical conditions for effective realization of educational process, development of appropriate training and methodological support of control and diagnostic tools. The blocks of the model of future primary teachers' training to the formation of constructive skills (methodologically-target, organizational-procedural and productive) are identified and justified. It is represented the effectiveness of implementing author's models that provide certain pedagogical conditions: the formation of internal positive motivation to the formation of constructive skills; optimization of educational process through the integration of artistic and technological disciplines in the training course "Employment training workshop", which leads to the formation of constructive skills of future primary school teachers; the formation of creative educational environment in educational process of the university;the development of professional skills of future primary school teachers during pedagogical practice and the implementation of scientific research works.